mCRP as a Biomarker of Adult-Onset Still’s Disease: Quantification of mCRP by ELISA - Fujita, Chitose; Sakurai, Yasuo; Yasuda, Yuki; Homma, Rino; Huang, Cheng-Long; Fujita, Masaaki (Frontiers in Immunology, 2022)
Background: C-reactive protein (CRP) is a dynamic protein that undergoes conformational changes between circulating native pentameric CRP (pCRP), pentameric symmetrical forms (pCRP*) and monomeric (or modified) CRP (mCRP) forms. mCRP exhibits strong pro-inflammatory activity and activates platelets, leukocytes, and endothelial cells. Abundant deposition of mCRP in inflamed tissues plays a role in several disease conditions, such as ischemia/reperfusion injury, Alzheimer’s disease, and cardiovascular disease. Although pCRP is typically quantified rather than mCRP for clinical purposes, mCRP may be a more appropriate disease marker of inflammatory diseases. Therefore, simple methods for quantifying mCRP are needed. Methods: We developed a specific enzyme-linked immunosorbent assay (ELISA) to measure plasma levels of mCRP. Plasma mCRP concentration was measured in patients with adult-onset Still's disease (AOSD) (n=20), polymyalgia rheumatica (PMR) (n=20), rheumatoid arthritis (RA) (n=30), infection (n=50), and in control subjects (n=30) using the developed ELISA. Results: We demonstrated that mCRP is elevated in some inflammatory autoimmune diseases, particularly AOSD. The mCRP concentration was also significantly higher among AOSD patients than RA, PMR patients and controls (477 ng/ml, 77 ng/ml, 186 ng/ml, and 1.2 ng/ml, respectively). Also, the mCRP (×1,000)/pCRP ratio was significantly higher among AOSD patients than RA, PMR, and infection patients (3.5, 0.6, 1,6, and 2.0, respectively). Conclusion: The plasma mCRP levels are elevated in some autoimmune diseases, particularly AOSD. The plasma mCRP levels may therefore be a potentially useful biomarker for AOSD.